The Impact of exchange rate volatility on international trade - NYUNT, Lwin Khaing (KDI School, 2019)
This study analyses the association between the exchange rate instability and external trade (exports & imports) of AMSs whether negative effect or positive effect or not. We use Generalized Moment Method for statistical test and GARCH models for the measurement of EXV. This study examined to investigate how exchange rate instability on exports and imports of rich and poor countries in Asia. This study applies the annual panel data for the time frame of 2008 to 2017. The result of this study confirms the inverse linkage between the exchange rate instability and the changes in the exports volume and the imports volume, and even in this case, the magnitude is generally small. The estimation shows that the increased in REER will induce exports and imports and TOT increase on exporting and decrease on exporting. The increasing of GDP and inflation will cause a higher volume of exports and imports. The FDI is a positive significant effect on exports as well. The study summarizes that monetary policy can take the actions to diminish the exchange rate uncertainty and fiscal policy as well.
Thesis(Master) --KDI School:Master of Public Policy,2019